(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2018)
The following review article undertakes the defense of the meaning and position of the real definition, in particular the classical one, through a polemic with the thesis of Robert Kublikowski’s work Definicje i rozwój wiedzy.Od Arystotelesa do Putnama (Definitions and Development of Knowledge. From Aristotle to Putnam). The author of the above-mentioned work undertook an extremely important task of examining the status and role of the real, and in particular the classical, definition in scientific applications, polemicising with some theses of modern philosophers of science, such as: Karl Popper, Hilary Putnam, or the theoretician of communication Edward Schiapp. Although the work of R. Kublikowski presents and refers to many thinkers of modernity and antiquity, including the concepts of Aristotle himself, the author essentially builds his arguments in relation to Popper’s position of fallibilism, antiessentialism and anti-definitionalism. It seems, however, that the author only partially defended the position of certitude and definitionism, which he tried to prove. The author of the discussed monograph referred only to natural and genre concepts, but the work would gain value if he extended his considerations onto the area of general theory of being, which Stagirite considered the highest and certain kind of theoretical knowledge, called episteme by him.